High Circulating Follicle-Stimulating Hormone Level Is a Potential Risk Factor for Renal Dysfunction in Post-Menopausal Women - Li, Qihang; Zheng, Dongmei; Lin, Haiyan; Zhong, Fang; Liu, Jing; Wu, Yafei; Wang, Zhixiang; Guan, Qingbo; Zhao, Meng; Gao, Ling; Zhao, Jiajun (Frontiers in Endocrinology, 2021)
Objective: Menopause contributes to renal dysfunction in women and it is generally attributed to oestrogen withdrawal. In addition to decreased oestrogen levels, serum follicle-stimulating hormone (FSH) levels also increase substantially after menopause. We investigated the association between high circulating FSH levels and renal function in postmenopausal women. Methods: This was an observational cross-sectional study included 624 pre-menopausal, 121 peri-menopausal, and 2540 postmenopausal women. The levels of female sex hormones were examined by chemiluminescent methods and the indices of renal function were examined using a Beckman AU5800 Chemistry analyser system. The main analyses assessed postmenopausal women divided by serum FSH quartiles. Results: Comparisons among women from pre-menopause to peri-menopause to post-menopause showed obvious stepwise recessions in renal function had accompanied by increasing serum FSH levels. In postmenopausal women, with increasing FSH quartiles, the serum creatinine (Scr) levels gradually increased, corresponding with the gradual decrease in the estimated glomerular filtration rate (eGFR) (p for trend < 0.001); moreover, both the prevalence of declined eGFR (eGFR < 90 ml/min/1.73 m2) and chronic kidney disease (CKD, eGFR < 60 ml/min/1.73 m2) gradually increased (p for trend < 0.001). Even after adjusting for vital confounders, both odds ratios (ORs) of decreased eGFR and CKD increased with increasing FSH quartiles. The ORs of declined eGFR (OR = 2.19, 95% CI: 1.63–2.92) and CKD (OR = 10.09, 95% CI: 2.28–44.65) in the highest quartile of FSH increased approximately twofold and tenfold compared with that in the lowest quartile (p < 0.05), respectively. After stratifying postmenopausal women by median age (61 years), the OR of decreased eGFR for each FSH quartile in the older group was higher than that for the corresponding FSH quartile in the younger group. Conclusions: A high circulating FSH level was an independent risk factor for renal dysfunction in women after menopause and the adverse effects of FSH on renal function worsened with ageing. Key words: FSH, menopause, eGFR, CKD, renal dysfunction, ageing